ECOLOGICAL AND GEOCHEMICAL ESTIMATION OF THE SPREADING OF TECHNOGENIC ELEMENTS IN THE TERRITORY OF KIVERTSIV NATIONAL NATURAL PARK "TSUMANSKA PUSHCHA" - Сплодитель, A. (Київський національний університет імені Тараса Шевченка, 2021)
Analysis of heavy metals content in the soils of the territory showed its heterogeneous distribution and dependence on available sources of technogenic impact. Geochemical accumulation coefficients were calculated and analyzed. The highest concentrations of manganese and chromium are in soils developed on forest deposits. The highest concentrations of nickel and copper are in soils developed on water-glacial deposits. Most of the studied heavy metals exceed the regional geochemical background. In terms of gross content in soils, trace elements form the following geochemical series: Zn> Cu> Pb> Ni> Mn> Cr. Accumulation of lead in forest deposits up to 2-3 MPC was defined. Most heavy metals in the soil are nonuniformity distributed. High values of the variation coefficient (V) – more than 34 % – are typical for inhomogeneous set of data on the concentrations of all investigated heavy metals. The highest index of variation was defined for lead concentration and equal to 170%, the lowest values were obtained for chromium content and equal to 34 % and zinc – 36 %. In the investigated soils there are two types of micronutrient distribution: elements accumulation in organic horizons with concentration decrease in the lower part of the profile and distribution by sedentary – illuvial type. The first type is characterized by increasing distribution of the following elements Zn, Pb; the second one is characterized Co, Ni, Cu, Mn. The ecological and geochemical assessment of technogenic elements distribution of the NNP Tsumanska Pushcha territory is made on the basis of the comparison of technogenic geochemical specialization of different environments (water, soils, etc.). For assessing the role of landscape components in the general geochemical anomaly of the territory, it is proposed to create total ecological and geochemical estimations. It represents the total values of pollutant concentration coefficients in individual components. Further researchers should focus on the analysis of macronutrients and genetic types of soils; determination of the reference content of elements in geochemical landscapes for defining intensity migration and characteristics of elements distribution; conducting biogeochemical zoning.

Розглянуто особливості акумуляції та розподілу забруднювальних речовин у ландшафтах КНПП "Цуманська Пуща" в умовах природних і техногенних геохімічних аномалій. Аналіз вмісту важких металів у ґрунтах території засвідчив неоднорідний розподіл та залежність від наявних джерел техногенного впливу. Проаналізовано масив даних та розраховано геохімічні коефіцієнти накопичення основних забруднювачів. Найвищі концентрації марганцю та хрому мають ґрунти, що розвинуті на лесових відкладах, а нікелю та міді – на воднольодовикових відкладах. Більшість досліджуваних важких металів перевищує регіональний геохімічний фон. За валовим вмістом у ґрунтах мікроелементи формують такий геохімічний ряд: Zn>Cu>Pb>Ni>Mn>Cr. Чітко простежується накопичення в лісових підстилках свинцю – до 2–3 ГДК. Більшість важких металів у ґрунтовому покриві розподілені нерівномірно. Високі значення коефіцієнта варіації – понад 34 % – характерні для неоднорідної сукупності даних щодо концентрацій всіх досліджуваних важких металів. Найвищий показник варіації виявлений для концентрації свинцю – 170 %, найменші значення отримані для вмісту хрому – 34 % і цинку – 36 %. У вивчених ґрунтах спостерігається два типи розподілу мікроелементів: акумуляція елементів в органічних горизонтах з поступовим зменшенням концентрації в нижній частині профілю та розподіл за елювіально-ілювіальним типом. Для першого типу характерний зростаючий розподіл – Zn, Pb, для другого – Co, Ni, Cu, Mn. Виконано еколого-геохімічну оцінку розподілу техногенних елеметів території КНПП "Цуманська Пуща" на основі порівняння техногенної геохімічної спеціалізації різних середовищ (вода, ґрунти тощо). Для оцінки ролі компонентів ландшафту в загальній геохімічній аномальності території запропоновано створювати сумарні еколого-геохімічні оцінки, що представляють суму значень коефіцієнтів концентрації полютантів в окремих компонентах. Основним напрямом подальших досліджень має бути вивчення розподілу макро- та мікроелементів у різних генетичних типах ґрунтів; визначення еталонного вмісту елементів у геохімічних ландшафтах для встановлення інтенсивності міграції та характеру розподілу елементів; проведення біогеохімічного районування.
ЕКОЛОГО-ГЕОХІМІЧНА ОЦІНКА РОЗПОДІЛУ ТЕХНОГЕННИХ ЕЛЕМЕНТІВ НА ТЕРИТОРІЇ КІВЕРЦІВСЬКОГО НАЦІОНАЛЬНОГО ПРИРОДНОГО ПАРКУ "ЦУМАНСЬКА ПУЩА"
Keywords: валовий вміст; техногенні елементи; коефіцієнти накопичення; gross content; technogenic elements; accumulation coefficients